Etiopathogenesis of lifestyle disorders: Preventive insights from swasthavritta and Diagnostic perspective from Roga Nidana - Sharma, Sagar; Sahu, Renuka (Journal of Neonatal Surgery, 2025)
Lifestyle disorders, known as non-communicable illnesses, and it is significant health challenge worldwide which usually result from prolonged disruptions in food, physical activity, mental discipline, and daily routines. Ayurveda, being an ancient medical science, offers a holistic framework for lifestyle disorders through an integrated perspective of the body, mind, and lifestyle. As per Ayurvedic classics, diseases primarily arise from prajnaparadha, asatmyendriyartha samyoga and parinama resulting in dosha–dushya sammurchana and the subsequent manifestation of disease. Lifestyle disorders, including obesity, diabetes, hypertension, mental illnesses, and osteoporosis, are primarily santarpanajanya vyadhis arising from chronic over-nourishment, sedentary behaviour, stress, and disturbance of biological cycles. Present article examines the etiopathogenesis of lifestyle problems from an Ayurvedic viewpoint and emphasises the significance of the Roga Nidana for early diagnosis and disease staging via nidana, purvarupa identification, samprapti analysis, and rogi–roga pariksha. The role of swasthavritta practices such as dinacharya, ritucharya, ahara-vihara, rasayana, sadvritta, and panchakarma in the prevention and management of lifestyle disorders..